The Role of Sex in Malaria-COVID19 Coinfection and Some Associated Factors in Rivers State, Nigeria - E. O. Onosakponome; M. N. Wogu (Journal of Parasitology Research)
Objectives. Data on the coinfection of malaria and COVID-19 is highly limited especially in Africa due to the novel nature of the pandemic COVID-19. Malaria and COVID-19 share striking similarities in their symptoms. A cross-sectional randomized study was conducted to investigate the role of sex in the coinfection of malaria and COVID-19 as well as some associated factors in Rivers State, Nigeria. Methods. Ethical approval was obtained from the Rivers State Health and Ethics Committee before the commencement of this study, and the study was conducted at the COVID-19 Treatment Center Medical Laboratory, Rivers State, Nigeria. Intravenous blood samples from three hundred randomly selected consenting study participants were examined for Plasmodium species using Giemsa microscopy, while pretested questionnaires were used to obtain data on sex, risk factors, and symptoms. All data generated were analyzed statistically using the Chi-square test with a P<0.05 value considered significant. Results. All study participants had Plasmodium species (100% prevalence) with varying parasite loads, and P. falciparum was the only species observed. Study participants (irrespective of sex) with low and high parasitaemia had the highest and least prevalence, respectively (P>0.05). Male study participants experienced more symptoms than females (P>0.05) except for sore throat which had an equal value among males and females. Travel history was the only risk factor that showed significant association with sex, and males had a higher value than females (P<0.05). Conclusion. Malaria and COVID-19 are major public health issues in Nigeria; more researches on these diseases especially in epidemiology, pathology, diagnosis, treatment, and vaccine production are vital.